To find the point of intersection between the two equations, we can set them equal to each other and solve for x:
-13x - 4 = 3x + 6
-13x - 3x = 6 + 4
-16x = 10
x = -10/16
x = -5/8
Now that we have x, we can substitute it back into either equation to solve for y. Let's use the first equation:
y = -13(-5/8) - 4
y = 65/8 - 4
y = 65/8 - 32/8
y = 33/8
Therefore, the point of intersection between the two equations is (-5/8, 33/8).
y=-13x-4
y=3x+6
3 answers
would it be
one solution
no solution
or infinite solutions
one solution
no solution
or infinite solutions
Since we found a specific point of intersection (-5/8, 33/8), there is one unique solution for the system of equations. So, the correct answer is one solution.